nbendavid1/siberia_lai: Tree and Shrub LAI Analysis from Northeast Siberia - Davi Bendavid; Mike Loranty; Omshi Samal (Zenodo, 2022)
This code is the processing and analysis of Leaf Area Index data from field sites near Cherskiy, Russia. These analyses were done at Colgate University in the Department of Geography, Loranty Lab.